Development Of A Web-Based E-Presence Application For Tracking Maps And Selfies Using Laravel - Suherman, Asep; Ibrahim, Rohmat Nur; Seftiansyah, Rifan; Idzharulhaq, Zaidan (Brilliance: Research of Artificial Intelligence, 2024)
Attendance is an activity aimed at assessing the level of employee presence and discipline within an organization or company. The E-Presence application is developed as a tool to enhance efficiency, accountability, and transparency in employee attendance, as well as to facilitate the processing of attendance data The E-Presence application aims to reduce errors and improve the accuracy of employee attendance records, which are crucial for the decision-making process. The development of the E-Presence application uses the Laravel framework, MySQL database, and UML (Unified Modeling Language) tools to design Use Case Diagrams, Activity Diagrams, and Class Diagrams. The system development method follows the waterfall model, and Black Box Testing is employed as the testing method. The urgency of this research lies in the system's ability to perform real-time attendance tracking that can be conducted outside the office within a maximum distance of 20 meters. With the implementation of tracking maps, employees do not need to queue, thereby increasing work efficiency. Attendance recording can be done in real time, is flexible, easily accessible, improves efficiency in attendance recording, reduces the potential for errors, enhances human resource management, and provides attendance reports in Excel format. The novelty of this research is the development of a web-based application that incorporates Tracking Maps and Selfie features, ensuring that employees must be in a designated area to check in. Thus, the company/organization can easily analyze and evaluate employee discipline. The testing results indicate that the application functions well and meets user needs.